Utilizing Duolingo Application as a Learning Media in Teaching English to Enhance the Students’ Vocabulary Mastery of the Second Grade SMPIT Bina Insan Parepare - Istiqamah As'ad, Nurul; Latifa, Ammang; Larekeng, Sitti Hajar (STAIN Majene, 2023)
Vocabulary is a list of words in a particular language. The objective of this research is to find out the effectiveness Duolingo application for enhancing the students’ vocabulary mastery of the second grade SMPIT Bina INSAN Parepare and its effect on students’ vocabulary achievement. The design of this research was experimental research which belongs to the quantitative method. The population of this research was the entire second-grade SMPIT Bina INSAN Parepare. There were two classes, they were VIIIB consisted of 25 students who got treatment using Duolingo application and VIIIA consisted of 26 students who got treatment using conventional teaching. Then, the data were analyzed by using SPSS (Statistical Product and Service Solutions) for Windows version 22.0. The results of this study showed that students had a positive motivation to Duolingo as English learning media in Android. The participants stated that Duolingo is easy to be used. The results of this study also revealed that learning English through Duolingo in Android was attractive to motivated learners who had no interest in learning English. Next, the results of this study showed that both participants from the interview tended to keep using Duolingo as English learning media in Android.